A female teacher voice in a symbolic order: a phenomenological inquiry - Ryan, Elizabeth (Curtin University, 2013)
This thesis is a phenomenological exploration of the role of education in the creation of the term “woman” in a gendered society. Through linguistic, dramatic and poetic presentations of lived experiences of females, I seek to understand a gendered societya Symbolic Order.I explore the power of a woman’s voice, the ways by which women and girls learn to use their voices, and how they might be haunted by the question Zizek asks,“Chez Vuoi? What do you want of me?”